The association between socioeconomic distress communities index and amputation among patients with peripheral artery disease - Witrick, Brian; Shi, Lu; Mayo, Rachel; Hendricks, Brian; Kalbaugh, Corey A. (Frontiers in Cardiovascular Medicine, 2022)
Background: Socioeconomic factors have been shown to be associated with amputation in peripheral artery disease (PAD); however, analyses have normally focused on insurance status, race, or median income. We sought to determine whether community-level socioeconomic distress was associated with major amputation and if that association differed by race. Methods: Community-level socioeconomic distress was measured using the distressed communities index (DCI). The DCI is a zip code level compositive socioeconomic score (0-100) that accounts for unemployment, education level, poverty rate, median income, business growth, and housing vacancies. A distressed community was defined as a zip code with DCI of 40 or greater. We calculated one-year risk of major amputation by DCI score for individuals with peripheral artery disease in South Carolina, 2012-2017. Treating death as competing event, we reported Fine and Gray subdistribution hazards ratios (sdHR), adjusted for patient demographic and clinical factors associated with amputation. Further analyses were completed to identify potential differences in outcomes within strata of race and DCI. Results: Among 82,848 individuals with peripheral artery disease, the one-year incidence of amputation was 3.5% (95% CI: 3.3%, 3.6%) and was significantly greater in distressed communities than non-distressed communities (3.9%; 95% CI: 3.8%, 4.1% vs 2.4%; 95% CI: 2.2%, 2.6%). After controlling for death and adjusting for covariates, we found an increased hazard of amputation among individuals in a distressed community (sdHR: 1.25; 95% CI: 1.14, 1.37), which persisted across racial strata. However, regardless of DCI score, Black individuals had the highest incidence of amputation. Conclusions: Socioeconomic status is independently predictive of limb amputation after controlling for demographic characteristics and clinical comorbidities. Race continues to be an important risk factor, with Black individuals having higher incidence of amputation, even in non-distressed communities, than White individuals had in distressed communities.